Chemical factors in neural growth, degeneration, and repair - Bell, Christopher, 1941-2008 (Elsevier, 1996)
This volume provides an up-to-date survey of current thinking concerning the actions of chemical factors in the regulation of neuronal behaviour under normal and pathological conditions. The book is divided into four sections, dealing with chemical factors involved with the formation of axon pathways, factors involved with neuronal survival and specialization during normal development, factors involved in normal maintenance and repair of adult neurons and, finally, factors that have been implicated as mediators of degenerative changes in neurological and neuropsychiatric disorders.